THE SINERGY OF CONVENTIONAL AND ONLINE TRANSPORTATION - Ashinta Sekar Bidari (Surakarta Law and Society Journal, 2018)
Technological and information developments have brought changes to the economy. The community begins to innovate in business by utilizing internet media. Information and communication technology has experienced rapid development over time. Technology is one of the factors that can change the social dynamics of society. With the emergence of a variety of new technologies, many companies and businesses are being innovated to create attractive business models with services that are no less amazing. One of the current technological developments is in online motorcycle taxi services. With the presence of online transportation, there must be a good synergy with conventional transportation. Good synergy is expected to create healthy competition between the two modes of transportation. Keywords: Synergy, Conventional Transportation, Online Transportation